Soil fungi respond more violently to both polyethylene and PBAT biodegradable mulch film residues than bacteria do - Liu, Liyuan; Li, Liuliu; Zou, Guoyuan; Gu, Jialin; Zuo, Qiang; Zheng, Xiangqun; Du, Lianfeng; Liu, Dongsheng (Frontiers in Environmental Science, 2025)
Biodegradable mulch film (BDM) residues in farmland have attracted extensive concern due to their low degradation rate in soil after the service period. However, different reactions of the bacterial and fungal communities to LDPEM and BDM residues have been confusing. A pot experiment was implemented to explore the influences of 0.5% and 2.0% (w/w) LDPEM and BDM residues on soil physicochemical properties and bacterial and fungal communities in the present study. The results indicated that BDM residues significantly increased soil pH and SOC to an increasing degree under the treatment with a higher mulch film residue amount, while LDPEM residues did not. The dissimilarities of the bacterial community between the treatment groups and the control ranged from 0.24 to 0.27, while the dissimilarities of the fungal community were higher, with the variation ranging from 0.43 to 0.46. Higher variations in the internal correlation coefficient were observed in the fungal community than in the bacterial community under the treatment groups. In addition, the modules of the bacterial community network increased from 2 to 3 under the BDM 0.5% and BDM 2.0%. Comparatively, the treatments with BDM residues doubled the modules of the fungal community network from 2 to 4. Structural equation modelling indicated that mulch film residues had a higher negative direct effect on fungal community structure (−0.752) than on bacterial community structure (−0.600). However, soil physicochemical properties had no significant influences on either bacterial or fungal communities. Overall, soil fungi respond more violently to mulch film residues than bacteria do.